When do venture capitalists add value? - Sapienza, Harry J. (Journal of Business Venturing, 1992)
Venture capitalists functioning as lead investors and the entrepreneur-CEOs of their portfolio companies responded to questionnaire surveys that asked them to rate the venture capitalists' involvement in the ventures. The perceived effectiveness of the investor's involvement weighted by its perceived importance was used as a proxy for the investor's value to the venture. The survey was administered in the early part of 1988. Eighty percent of venture capitalists and 85% of entrepreneurs surveyed responded; in all, 51 matched pairs of lead investor-CEO surveys were completed and returned. Over 50 hours of interviews were also conducted to help clarify information derived through the surveys. CEOs and venture capitalists rated the nature and intensity of their interaction as well as the performance of the venture over a one-year period. CEOs also provided data on strategy, level of innovation, environmental uncertainty, and their level of experience. Regression analyses indicated that a significant portion of variation in the value of venture capitalist involvement was explained by these factors. Specifically, the greater the innovation pursued by the venture, the more frequent the contact between the lead investor and the CEO, the more open the communication, and the less conflict of perspective in the venture capitalist-CEO pair, the greater was the value of the involvement. Neither the stage of the venture nor the CEO's experience had a significant impact on value added. The value of venture capitalists' involvement was also strongly positively correlated with venture performance. The implications for the venture capitalists include the following: (1) the value of involvement varies with circumstances; (2) the most effective venture capitalists are those who maintain frequent, open communications while minimizing conflict; (3) opportunities exist for adding value in all venture stages; and (4) both experienced and inexperienced CEOs can benefit. For entrepreneurs, three key findings are: (1) because venture capitalists can add value beyond the money supplied, choosing the right one at the outset is very important; (2) once in, it is important to keep communication channels open; and (3) high innovation ventures benefit most from venture capitalist involvement. The results are important because they provide insight into controllable circumstances that impact the value of venture capitalist involvement in their portfolio companies. Given the general economic conditions now facing entrepreneurs and the degree of cut-throat competition in the venture capital industry, such information may prove extremely useful to both as they plan strategies for the 1990s.